Hubungan Tingkat Pendidikan Dan Kepadatan Penduduk Dengan Tempat Penampungan Sementara (TPS) Ilegal Di Kota Tembilahan - Annisa Nur’alifa; Jecky Asmura; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Tembilahan is the capital city of Indragiri Hilir, it has 67.74 km2 area and has 89,404 population. The amount of garbage which has been increasing as long as the growth population. Social factors that influence waste management are factor of education and factor population density. The purpose of this study is to analyze the relationship between level education and population density towards ilegal dumping. This research was conducted with a survey method directly to the study area. The result were The education level of respondents towards illegal dumping increased as the increasing number of high school graduation respondents. Based on the histogram of population density comparison to the number of illegal dumping, high and low population density doesn’t affect the number of illegal dumping.Keywords : Ilegal dumping, level education, population density